(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Notes on the Concordat of Ponte Mammolo (April 11, 1111) This essay aims to highlight the historical importance of the Concordat of Ponte Mammolo (1111) in the context of the Investiture Controversy and at the same time to highlight the role played by the nascent concordatory institution in the relations between the Papacy and the Empire. First of all, a general overview of the historical and legal presuppositions of the Concordat is offered, retracing the events that led to its stipulation. The concordat text is then examined, highlighting its peculiar formal structure and then analyzing its material discipline. Constant reference is made to the contemporary Concordats of Sutri (1111) and Worms (1122) which also regulate the matters of investitures. SOMMARIO: 1. Premessa - 2. I presupposti storico-giuridici del Concordato - 3. La stipulazione concordataria - 4. Esame degli accordi - 5. Il Privilegio pontificio - 6. Sviluppi della vicenda - 7. La dichiarazione di nullità del Privilegio pontificio - 8. Considerazioni conclusive.